(untitled) (Journal SCIENCEVOLUTION, 2025)
Bronchiolitis is defined as the first episode of lower respiratory tract infection in patients under 2 years of age. Despite numerous studies, there is still insufficient data to draw firm conclusions regarding its efficacy (or lack thereof). For these reasons, a systematic review was conducted to evaluate the efficacy and safety of 3% nebulized saline solution in patients with acute bronchiolitis. A systematic review was performed following the PRISMA methodology. The search yielded 874 articles; after removing duplicates, screening titles/abstracts for relevance, and assessing content, 10 studies were selected. Several reviewed articles affirmed its effectiveness in reducing symptoms or clinical severity. Analysis of adverse effects confirmed a low occurrence of mild adverse reactions, or even their absence, with no serious adverse effects reported. The reviewed articles reported hospital stays ranging from 3.7 to 4 days and earlier hospital discharges. Despite significantly modifying these variables, it was generally reported that there is insufficient evidence of its effectiveness. It is concluded that it is a safe treatment in pediatric patients with bronchiolitis, associated with minor adverse events, but further studies are needed to confirm its efficacy.